2006
DOI: 10.1093/annonc/mdl035
|View full text |Cite
|
Sign up to set email alerts
|

Functional categories of TP53 mutation in colorectal cancer: results of an International Collaborative Study

Abstract: Mutations that inactivate the transactivational ability of TP53 are more frequent in advanced CRC and are associated with worse prognosis in this stage of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 12 publications
5
56
0
3
Order By: Relevance
“…3 The 5-year overall survival (OS) was 63%, with a median follow-up of 54.6 months. A clear prognostic value of the stage was observed in this series (see Supplemental Figure S1 at http://ajp.amjpathol.org).…”
Section: Clinical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…3 The 5-year overall survival (OS) was 63%, with a median follow-up of 54.6 months. A clear prognostic value of the stage was observed in this series (see Supplemental Figure S1 at http://ajp.amjpathol.org).…”
Section: Clinical Datamentioning
confidence: 99%
“…In a large cohort of colorectal carcinomas published by the TP53-CRC Collaborative Study Group, this prognostic impact seems intricate and depends on tumor site, type of mutation, adjuvant therapy, and stage of the disease. 3,4 Posttranslational modifications of the p53 protein, such as ubiquitination, phosphorylation, and acetylation, contribute to p53 activity regulation, leading to protein stabilization, conformational changes, and modifications of its affinity for DNA and its interaction with transcriptional coactivator complexes. 5 As a result, the molecular modulators of p53 could play a significant role by influencing the p53-dependent responses in tumor cells and altering the prognostic significance of the p53 genetic status of the tumor.…”
mentioning
confidence: 99%
“…Diep et al (2003) showed that TP53 mutations affecting the L3 zinc-binding domain and lower survival rate in the subclassification of Dukes' B and C patients and may have an impact on the ideal treatment strategy. However, the prognostic role of TP53-inactivating mutations is still in question (Iacopetta et al, 2006). Similarly, the impacts of epidermal growth factor receptor (EGFR) over-expression, loss of heterozygosity in chromosome 18q, somatic adenomatous polyposis coli (APC), and KRAS mutations on survival remain unclear (Diep et al, 2003;Spano et al, 2005;Walther et al, 2009).…”
Section: Molecular Markersmentioning
confidence: 99%
“…Many studies on CRC patients have shown evidence of the prognostic value of TP53 mutations/loss of function and its association with worse survival. [28][29][30] No robust evidence or consensus about predictive role of p53 in relation to treatment is yet available, and therefore p53 is not routinely used in clinical practice.…”
Section: Genetic Alterations In Tumor Tissuesmentioning
confidence: 99%